2009
DOI: 10.1111/j.1423-0410.2009.01196.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel system for storage of buffy‐coat‐derived platelet concentrates in a glucose‐based platelet additive solution: parameters and metabolism during storage and comparison to plasma

Abstract: PAS-G's novel presentation allows incorporation of glucose into the additive solution so that it is roughly equivalent to plasma for the maintenance of buffy-coat PCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…This AS has a low pH (5.2), and its composition has been previously described. 12 The ELX container is a non-polyvinyl chloride, non-Di(2-ethylhexyl) phthalate container composed of ethylene butyl acrylate copolymer and is in current use in Europe. 15 The product was stored overnight with horizontal agitation.…”
Section: Manufacture Of 18-to 24-hour Room Temperature-held Prp-derivmentioning
confidence: 99%
See 2 more Smart Citations
“…This AS has a low pH (5.2), and its composition has been previously described. 12 The ELX container is a non-polyvinyl chloride, non-Di(2-ethylhexyl) phthalate container composed of ethylene butyl acrylate copolymer and is in current use in Europe. 15 The product was stored overnight with horizontal agitation.…”
Section: Manufacture Of 18-to 24-hour Room Temperature-held Prp-derivmentioning
confidence: 99%
“…Details of this storage system have been previously published. 12,13,[15][16][17] The scheme is illustrated in ❚Figure 2❚ and allows the manufacture of paired products for comparison studies. Neither the AS nor the ELX containers are cleared by the FDA for use in platelet storage at present.…”
Section: Manufacture Of 18-to 24-hour Room Temperature-held Prp-derivmentioning
confidence: 99%
See 1 more Smart Citation
“…Saunders et al reported that the percentage of activated platelet was similar between platelets resuspended in additive solutions and platelets resuspended in 100% autologous plasma for up to 10 days of storage [37]. In the same way, Gyöngyössy et al founded that platelet concentrates resuspended in additive solution with glucose showed similar characteristics in activation (CD62P), morphology, pH glucose metabolism and swirl, when they were compared to platelets in plasma [38]. Ringwald et al [39] suggested that adding PAS immediately or 2 hours after the collection does not affect the in vitro activation and quality of stored platelets up to 7 days.…”
Section: Discussionmentioning
confidence: 89%
“…Since PMP were one of the constituents of PC units in blood banks and some biological functions have been attributed to these vesicles, we studied some determinants on their surface. Besides, additive solutions [14][15][16] like Composol were salt solutions for replacement of plasma in PC units. So in this research, PS exposure and the binding capacity of PMP to vWF were surveyed during 7 days storage of PCs in the media of plasma and Composol.…”
Section: Introductionmentioning
confidence: 99%